Interfacial Regulation of Electron‐enhanced Co2P−CuP2 Sheet‐like Heterostructure as a Robust Bifunctional Electrocatalyst for Overall Water Splitting and Zn−H2O Cell. Issue 6 (18th February 2022) - Wang, Lixia; Zhao, Yunru; Huang, Zhiyang; Rao, Xianfa; Guo, Man; Isimjan, Tayirjan Taylor; Yang, Xiulin
Abstract: Constructing the precious metal‐free bifunctional electrocatalysts for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is highly desirable for overall water splitting and energy conversion devices in an alkaline medium. Here, the interface regulation strategy aims to synthesize a sheet‐like Co2 P−CuP2 heterostructure supported on nickel foam (NF) through hydrothermal reaction, electrodeposition and phosphating treatment. The Co2 P−CuP2 /NF exhibits extraordinary electrocatalytic performance with overpotentials of 220 mV and 93 mV for OER and HER at a current density of 10 mA cm −2, respectively. Remarkably, an electrolyzer cell originated from Co2 P−CuP2 /NF electrodes required an ultralow cell voltage of 1.77 V@500 mA cm −2 and 2.38 V@1000 mA cm −2 for overall water splitting with prominent stability of at least 160 h. In addition, the Zn−H2 O cell is assembled with Co2 P−CuP2 /NF as the cathode, achieving a high power density of 19.8 mW cm −2 and long‐term stability of 120 h. The electron transfer between Co and Cu species in the Co2 P−CuP2 /NF heterojunction can effectively improve the interaction between the active sites and the intermediates, thereby enhancing the electrocatalytic activity. This work opens up new insights into the preparation of highly active and durable bimetallic phosphide catalysts for water splitting and Zn−H2 O cells. Abstract : Water splitting : A sheet‐like Co2 P−CuP2 heterostructure is successfully constructed on NF by consecutive hydrothermal, electrodeposition and phosphating treatment. The bifunctional Co2 P−CuP2 /NF catalyst demonstrates extraordinary HER and OER performance in overall water splitting and Zn−H2 O cell.